A Review and Update on the Biochemical Basis of Conscious Breathing (Pranayama) - Carlos, Aulesa; Sunil, Panchal (Journal of Alternative Medicine and Mind Body Practices, 2026)
Breathing has long been recognised as a vital process in Eastern traditions such as YOGA and Ayurvedic medicine, where Pranayama is regarded as a transformative practice that harmonises body and mind. While the East developed sophisticated systems of breath regulation for health and self-awareness, the West largely overlooked their significance until the late 19th and early 20th centuries. A group of pioneering physicians, sometimes referred to as "the pulmonauts", including Christian Bohr, Konstantin Buteyko, and Peter M Litchfield, explored the physiological foundations of respiration. They emphasised the benefits of slow, nasal breathing and its relationship to both physical and emotional well- being. In the 21st century, contemporary researchers and practitioners such as James Nestor, J. Patrick McKeown and Anders Olsson have expanded this understanding through the fields of biochemistry, physiology, and biomechanics. Their work has clarified the mechanisms underlying conscious breathing and refined ancient pranayama techniques. Integrating insights from both Eastern and Western traditions reveals that breathing is a central factor in maintaining homeostasis and emotional balance.
Keywords: Pranayama; pulmonauts; biochemical mechanisms; breathing; carbon dioxide; nitric oxide